Analysis of Water Losses in the Jimat Irrigation Area, Wonosobo Regency - Faqih, Nasyiin; Ulumudin, Fadhilah Ilham; Abdussalam, Ashal; Qomaruddin, Mochammad; Musthofa, Musthofa (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2025)
This study aims to analyze the actual irrigation water losses in the Jimat Irrigation Area, identify the factors causing irrigation water losses, and determine effective strategies to reduce water losses in the area. One of the important irrigation areas in this region is the Jimat Irrigation Area, which supplies water to 110 hectares of agricultural land. However, the effectiveness of water distribution is often hampered by significant water losses. The research methods used are descriptive evaluative and quantitative descriptive analysis. The descriptive evaluative method describes a study that evaluates the actual conditions of the study object. Meanwhile, the quantitative descriptive analysis method aims to accurately describe the characteristics of the study object.Based on the analysis and calculations, the Jimat Irrigation Area requires an actual irrigation water supply of 0.812 m³/second to serve its four tertiary canals, with the highest allocation going to Tertiary Channel 2 (0.465 m³/second) and the lowest to Tertiary Channel 4 (0.084 m³/second). However, only 54% of the initial discharge of the primary canal (1.702 m³/second at the Upstream Intake) actually reaches the agricultural land. A total of 46% of the water (0.686 m³/second) is lost along the primary network, with seepage accounting for 99.94% of the water loss, particularly in critical sections such as Primary Channel V, which lost 59% of its discharge. Meanwhile, the contribution of evaporation is minimal (0.06%) due to the limited water surface area and low daily evaporation rate (2.76 mm/day).